A Robust Controller for Upper Limb Rehabilitation Exoskeleton - Andrés Blanco-Ortega; Luis Vázquez-Sánchez; Manuel Adam-Medina; Jorge Colín-Ocampo; Arturo Abúndez-Pliego; Claudia Cortés-García; Carlos Daniel García-Beltrán (Applied Sciences, 2022)
In this paper, a portable exoskeleton for the rehabilitation of upper extremities of three degrees of freedom (DOF) is proposed. With these degrees of freedom, the exoskeleton provides the movements of flexion–extension and abduction–adduction of the arm and flexion–extension of the forearm. A robust generalized proportional integral (GPI) controller for trajectory tracking to provide smooth movements for rehabilitation with the exoskeleton is proposed. This controller only requires output measurements and is robust against different types of disturbances. Simulation results are presented in the MSC Adams® software environment in co-simulation with Matlab-Simulink® to show the controller’s performance against different types of disturbances. The results of a PID type controller are also contrasted with the results of the GPI controller.